Production of tumor necrosis factor and interleukin-1 by macrophages from human atheromatous plaques. - Tipping, P. G. (1993)
The production of cytokines by atheromatous plaque macrophages from human endarterectomy tissue was assessed in vitro by short-term cell culture and in situ by immunohistology. Macrophages were isolated from plaques of 14 patients undergoing carotid endarterectomy and 7 patients undergoing reconstructive procedures on atheromatous distal aortic and femoral arteries. Tumor necrosis factor (TNF) and interleukin 1 (IL-1) production by plaque macrophages and blood monocytes isolated concurrently from these patients was assessed. TNF release by macrophages from carotid plaques (0.39 +/- 0.12 ng/10(6) cells/24 hours) was significantly augmented compared to the release by corresponding blood monocytes (0.014 +/- 0.011 ng/10(6) cells/24 hours, P = 0.03), and by macrophages from noncarotid lesions (0.038 +/- 0.036 ng/10(6) cells/24 hours, P < 0.04). Cellular TNF expression by macrophages within carotid plaques was also more prominent than in noncarotid lesions. By contrast, IL-1 production by plaque macrophages from both carotid and noncarotid plaques was not augmented compared to blood monocytes, and only infrequent and low-intensity labeling for IL-1 was present on macrophages within plaques from either group. These results provide functional and immunohistological evidence for increased production of TNF but not IL-1 by activated macrophages, indicating local and selective augmentation of cytokine production within carotid plaques. This suggests that macrophages play an active role in the inflammatory response within atheromatous carotid plaques.